A Comparative Analytical Study of Counseling Needs Among Students of Physical Education and Sport Sciences | Tikrit University - Mahmood, Akram Hassan (Pubmedia Jurnal Pendidikan Olahraga, 2026)
This study attempted to identify the level of guidance needs among physical education and sports science students at Tikrit University, and to compare these guidance requirements with those of other physical education and sports science students at the same university. The researcher used the descriptive survey method, as it was good for the nature of the research problem: showing differences in guidance needs among physical education and sports science students at Tikrit University. The research population consisted of physical education and sports science students at Tikrit University during the academic year (2025-2026), totaling (1074) students distributed across four academic years (first year = 326 students, second year = 395 students, third year = 255 students, and fourth year = 97 students). A stratified sample of (230) students, representing (21.415%) of the original population, was selected. (30) of these students, representing (13.043%), were used to extract the scientific criteria. The main research sample consisted of (200) students, representing (86.956%) of the total research sample. The researcher used the Statistical method for the Social Sciences (SPSS) to analyze the results. The findings indicated that students in the first year exhibited the highest mean level of guidance needs compared with those in other academic levels. The results are showing that the first year students are needing more comprehensive guidance and awareness if they been compared to other academic levels. Statistically the indications are referred very strongly for the first year students, as well as there are important differences showing between second, third and fourth year students and the results are showing for the favor of second year students, this means that the guidance and awareness processes are gradually starting to decrease whenever the students are passing from one level to another in other words they when they starting adaptation more and more with surrounded environment they can live and act more closely with the elements. The researcher here is recommending to provide and design more training and guidance programs particularly for first year students in order they can learn, adapt, and understand the university life much better and closer as well as providing more experienced guidance instructors and trainers inside the educational institutions in order to solve the problems and requirements of the students depending on academic criteria.